Tools to Map Chain Inter-Organisational Systems - Storer, Christine; Taylor, D. (Wageningen Publishers, 2006)
When looking at chains of organisations to improve business processes, maps are used to simplify complex interactions into diagrams that can analysed visually. Chain maps ensure that those involved in the analysis understand all of the interactions and consequently the implications of changes that may be suggested. Maps can be used to identify problems and opportunities for improvement as well as the greatest obstacles to cooperation. Maps can be used as a tool in chains of organisations to develop strategies to improve the performance of the chain over time.When mapping interactions between organisations most diagrams are drawn simply by depicting the organisations or departments that interact with each other (e.g. Cadilhon et al. 2003, Gifford et al. 1998). They have been called 'zero level' diagrams in this paper as they indicate which organisation or department is involved. While they are useful to get a general overview of the chain, they do not provide any details of which people are involved nor the details of the interaction.More detailed 'process' or 'flow' diagrams have been used to track the movement of a physical product or information flow through each major process within an organisation and/or between organisations. For example value stream mapping tools are used to improve processes by documenting the flow of information and physical products for a single product as well as the time taken and other key information (e.g. Rother and Shook 1998, Womack and Jones 1996).There appears to be a gap in the chain mapping tools found in the literature. The zero level maps do not provide enough detail to make a considered judgement of the opportunities for improvement nor to identify the greatest obstacles to cooperation. While the detailed process diagrams assist in determining root causes of problems and what needs to be changed they have two problems. Firstly there is an assumption that the grounds for examining a particular process in detail was rationally decided and secondly such diagrams tend to ignore the relationship issues involved within the process. It is argued you need more than an implicit understanding of the detail of who is involved and the nature of relationships when in the early stages of the chain diagnostic analysis.This paper provides examples of how this relationship detail can be mapped by initially using zero level diagrams. These more detailed zero level maps are suggested to identify opportunities for improvement that may have the greatest strategic impact on the chain as well as to highlight likely obstacles to cooperation. Multiple level relationship diagrams can then be used to identify the departments and the organisational hierarchical levels involved in these interactions so a team to work on the problem or opportunity can be established. Then the detailed process diagrams can be used for the detailed problem solving work. It is expected the mapping tools presented in this paper will be complementary to existing zero level mapping tools and the more detailed process mapping tools such as value stream mapping, by providing a framework with which to systematically evaluate key aspects of supply chain relationships.